2019
DOI: 10.2967/jnumed.119.231308
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Preclinical PET/CT Imaging to Improve Quantitative Accuracy, Precision, and Reproducibility: A Multicenter Study

Abstract: Preclinical PET/CT is a well-established noninvasive imaging tool for studying disease development/progression and the development of novel radiotracers and pharmaceuticals for clinical applications. Despite this pivotal role, standardization of preclinical PET/CT protocols, including CT absorbed dose guidelines, is essentially nonexistent. This study (1) quantitatively assesses the variability of current preclinical PET/CT acquisition and reconstruction protocols routinely used across multiple centers and sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Most recently, Greenwood et al [12] characterized a commercial four-chamber bed on a Mediso preclinical PET scanner, using NEMA phantoms and mice. As in previous studies, they demonstrated a decrease in uniformity and recovery coefficients, and an increase in spillover ratios, in the multiple vs. single animal cases, though these increases were within the recently suggested limits for bias [13].…”
Section: Introductionsupporting
confidence: 80%
“…Most recently, Greenwood et al [12] characterized a commercial four-chamber bed on a Mediso preclinical PET scanner, using NEMA phantoms and mice. As in previous studies, they demonstrated a decrease in uniformity and recovery coefficients, and an increase in spillover ratios, in the multiple vs. single animal cases, though these increases were within the recently suggested limits for bias [13].…”
Section: Introductionsupporting
confidence: 80%
“…Arguably the expected high 18 F-FDG uptake by the myocardium and brain may have affected SUV quantification in bones in close proximity to these organs (namely sternum and skull) due to spill-over measurement errors. However, these are expected to contribute to a maximum of 10% quantitative bias, as per measurements in our scanner using phantoms and standard acquisition protocols developed by our group (17).…”
Section: Site-specific Metabolic Differences In Bones Identified By Wmentioning
confidence: 99%
“…Over the years, numerous reports have highlighted considerations in small-animal PET imaging ( 54 – 56 ). Unfortunately, despite some progress, there are still gaps in standardization of small-animal imaging protocols and QI methods to produce consistent results as highlighted by recent works ( 119 , 120 ). Importantly, in line with the theme of this communication, there is a need to harmonize preclinical and clinical PET QI pipelines so as to enhance the translational impact of developments in PET imaging.…”
Section: Co-clinical Imaging Study Design Instruments and Standardimentioning
confidence: 99%
“…Lack of reproducibility in preclinical cancer research, including imaging, has been highlighted by numerous publications ( 119 , 166 ). Other than promoting open science, data sharing has been suggested as one solution to address reproducibility.…”
Section: Informatics Needs To Support Co-clinical Researchmentioning
confidence: 99%